The Impact of Age of Entry on Academic Progression - Julio Cáceres-Delpiano; Eugenio P. Giolito (Institute for the Study of Labor (IZA), 2014)
Using an RD-design and public educational administrative data for Chile, we study the impact of age of entry on children outcomes. Different from previous studies, we are able to track this impact on school achievements over eleven years of the school life of a cohort of students. Our results confirm previous findings that a higher age of entry not only has a positive effect on GPA and the likelihood of passing a grade but also that this impact tends to wear off over time. However, we also find that this impact on school achievement is still present eleven years after a child has started school. Moreover, we show that this decrease in the impact on GPA masks a return associated to a higher age of entry in other dimensions. First, we show that age of entry reduces the probability of being enrolled in a public school. Secondly, during secondary school, children delaying school entry are more likely to follow an academic track and we present evidence that these children are more likely to be enrolled in schools where children coming from other schools had a higher than the mean GPA in the school of origin. Finally, also explaining the decline in the impact of age of entry on school's achievements, we find evidence that age of entry is associated to an increase in the probability that a child is enrolled in a school actively engaged in cream skimming.
Keywords: A21; I24; I25; I28; 330; age of entry